On-chip quantum key distribution over field-deployed fiber using lithium niobate photonic circuit - Hyungjun Heo; Min Ki Woo; Chang-Hoon Park; Hyeong-Soon Jang; Hyeon Hwang; Hansuek Lee; Min-Kyo Seo; Sangin Kim; Hyounghan Kwon; Hojoong Jung; Sang-Wook Han (APL Photonics)
Quantum key distribution (QKD) systems have proven their theoretically unconditional security by quantum mechanics, but the scalability and cost barriers limit the rapid growth of the QKD system industry. The integration of QKD systems on chips has enabled their widespread adoption in secure quantum communication technologies, but the optimized platforms and designs are still being studied. Herein, we fabricated monolithic quantum photonic circuits for the BB84 QKD protocol using thin-film lithium niobate (TFLN), which enables flexible design in organizing both active and passive elements on one chip based on its superior material properties. The proposed circuit design for both transmitter and receiver parts are identical, which facilitates stable operation and mass production. Using our device, we demonstrated QKD over a field-deployed quantum channel, and its performance is comparable to state-of-the-art. This result proved the potential of TFLN for quantum communication technology.